Social protection coverage toolkit - Fabianna Bacil; Charlotte Bilo; Wesley de Jesus Silva (International Policy Centre for Inclusive Growth (IPC-IG), 2020)
The implementation of nationally appropriate social protection systems for all has emerged as one of the key targets of SDG 1, calling for all countries to report on the coverage of social protection programmes. Most approaches to measure social protection coverage take a 'participation' approach, meaning who participates (either directly or indirectly) in a social protection programme. However, they do not tell much about the extent to which people's specific life cycle risks are covered. This toolkit proposes an alternative approach to measuring social protection coverage, analysing the extent to which people's risks are covered, ranging from unprotected to protected.
Keywords: 330; social protection; coverage; life cycle risks; SDG 1.3